The roots of low European employment: family culture? - Yann Algan; Pierre Cahuc (Institute for the Study of Labor (IZA), 2005)
OECD countries faced largely divergent employment rates during the last decades. But the whole bulk of the cross-national and cross-temporal heterogeneity relies on specific demographic groups: prime-age women and younger and older individuals. This paper argues that family labor supply interactions and cross-country heterogeneity in family culture are key for explaining these stylized facts. First we provide a simple labor supply model in which heterogeneity in family preferences can account for cross-country variations in both the level and the dynamics of employment rates of demographic groups. Second, we provide evidence based on international individual surveys that family attitudes do differ across countries and are largely shaped by national features. We also document that cross-country differences in family culture cause cross-national differences in family attitudes. Studying the correlation between employment rates and family attitudes, we then show that the stronger preferences for family activities in European countries may explain both their lower female employment rate and the fall in the employment rates of young and older people.
Keywords: J21; J22; Z13; 330; employment rate; culture; family attitudes; Beschäftigung; Arbeitsangebot; Familienökonomik; Familiensoziologie; Schätzung; EU-Staaten; OECD-Staaten